2019
DOI: 10.1080/13607863.2019.1599816
|View full text |Cite
|
Sign up to set email alerts
|

Mediating the relationship between loneliness and cognitive function: the role of depressive and anxiety symptoms

Abstract: Objective: To evaluate the relationship between loneliness and cognitive functioning, and whether depressive and anxiety symptoms have intermediate roles therein. Methods: Information about 7,433 participants of the Irish Longitudinal Study on Ageing (a prospective, representative cohort study), aged over 50, was collected at three time-points two years apart, and analysed using Structural Equation Modelling to assess whether depressive and anxiety symptoms mediate the relationship between loneliness and cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…In different groups, anxiety can affect depression levels by acting on loneliness ( Ebesutani et al, 2015 ). The correlation analysis verified the findings of the predecessors that loneliness has a significant positive predictive effect on anxiety and depression ( Ostovar et al, 2016 ; McHugh Power et al, 2020 ). Interpersonal theories of depression indicate that positive interpersonal relationships are a protective factor for reducing individual depression ( Hammen, 1999 ) and that autistic patients often show negative interpersonal relationships.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In different groups, anxiety can affect depression levels by acting on loneliness ( Ebesutani et al, 2015 ). The correlation analysis verified the findings of the predecessors that loneliness has a significant positive predictive effect on anxiety and depression ( Ostovar et al, 2016 ; McHugh Power et al, 2020 ). Interpersonal theories of depression indicate that positive interpersonal relationships are a protective factor for reducing individual depression ( Hammen, 1999 ) and that autistic patients often show negative interpersonal relationships.…”
Section: Discussionsupporting
confidence: 81%
“…Some studies demonstrated through empirical research that loneliness, depression, and anxiety are inextricably linked ( Richardson et al, 2017 ; Michalska da Rocha et al, 2018 ). A significant correlation analysis found a positive correlation between loneliness, anxiety, and depression ( Jing et al, 2012 ; Ostovar et al, 2016 ; McHugh Power et al, 2020 ). A previous study showed loneliness had a significant mediating effect on anxiety and depression ( Ebesutani et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising, given the tight relationship between touch and feelings of loneliness [10,37], but also between feelings of loneliness and anxiety (e.g. [69][70][71]). Taken together, these findings suggest that the effects of lack of intimate touch on loneliness go above and beyond the effects of touch on anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found other important methodological novelties in more recent studies. In some studies, structural equation modelling was used rather than regression analyses to test linear causal relationships among variables, thus simultaneously accounting for measurement errors [ 15 , 64 , 65 ]. This modelling technique is key to estimate causal mechanisms more accurately, especially in contexts in which reverse causality and varying possible causal paths need to be jointly assessed.…”
Section: Discussionmentioning
confidence: 99%